Verification, Model Checking, and Abstract Interpretation 12th International Conference, VMCAI 2011, Austin, TX, USA, January 23-25, 2011. Proceedings - Jhala, Ranjit; Schmidt, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 12th International Conference on Verification, Model Checking, and Abstract Interpretation, VMCAI 2011, held in Austin, TX, USA, in January 2011, co-located with the Symposium on Principles of Programming Languages, POPL 2011. The 24 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 71 initial submissions. The papers showcases state-of-the-art research in areas such as verification, model checking, abstract interpretation and address any programming paradigm, including concurrent, constraint, functional, imperative, logic and object-oriented programming. Further topics covered are static analysis, deductive methods, program certification, debugging techniques, abstract domains, type systems, and optimization.
Keywords: Computer science; Software engineering; Computer software; Logic design; Computer Science; Logics and Meanings of Programs; Software Engineering; Programming Languages, Compilers, Interpreters; Algorithm Analysis and Problem Complexity; Mathematical Logic and Formal Languages; Programming Techniques